Identificação de relações de metacontingências e macrocontingências, conforme os critérios propostos por Malott e Glenn (2006) - Julio, Flávia Matielli (2008)
Often, the environment that has a behavioral function for us is the behavior of others (Glenn, 1991). This means that there is a similarity between the behavior's content of different individuals, characterizing a cultural practice (Glenn, 2004). The concepts of macrocontingência, and metacontingência characterize the contingencie's relation contained in these cultural practices and serve as "tools" to examine the culture. Considering that the before mentioned concepts are recent and that relatively few researches have employed them, the present study evaluated Malott and Glenn's (2006) proposal to classify interventions as involving either: operant contingency, macrocontingency, metacontingency or no selection of contingencies. For this evaluation, the path run by Malott and Glenn (2006) to classify the type of contingency intervention was, independently, remade for the researches classified as: operant contingencies, macrocontingencies or metacontingencies. Other articles were also classified. These articles were selected for addressing problems that involve several people. The results from this study showed that: (1) It was possible to identify the values of the criterion variables ("Number of people contributing to the product", "Variety of topographies contributing to product", "Product of interest", "Selecting consequence and Locus of change") from 16 of the 17 articles reviewed, but (2) it is necessary to consider that in analyses classified as containing relations of metacontingências, a detailed analysis for each relationship's component involved may reveal new relations, including macrocontingency. This study also showed that (3) it is not necessary to identify the five variables proposed to find the kind of contingency involved in researches